1978
DOI: 10.1136/thx.33.6.689
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol salbutamol administration by IPPB: lowest effective dose.

Abstract: Ruffin, R E, Obminski, G, and Newhouse, M T (1978). Thorax, 33,[689][690][691][692][693]. Aerosol salbutamol administration by IPPB: lowest effective dose. This study was conducted to determine whether small doses of salbutamol solution, aerosolised and delivered by intermittent positive-pressure breathing (IPPB), would be as effective as the 5 to 10 mg dose usually recommended for inhalational use. In nine asthmatic subjects we found that there was no significant difference between the peak bronchodilator eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The maximum dose deposited in the of 900 fig (20 fig/min for 45 min) (65), and had lungs is about 10% of that initially present in no side effects. The divergent findings may be the nebulizer (114). due to the much longer inhalation time (45 IPPB has been claimed to carry a definite risk min) used in the latter study.…”
mentioning
confidence: 77%
“…The maximum dose deposited in the of 900 fig (20 fig/min for 45 min) (65), and had lungs is about 10% of that initially present in no side effects. The divergent findings may be the nebulizer (114). due to the much longer inhalation time (45 IPPB has been claimed to carry a definite risk min) used in the latter study.…”
mentioning
confidence: 77%
“…Given the limited patient numbers, clinical judgment is paramount. Increasing from 2.5 to 5 mg salbutamol produces only limited incremental bronchodilation (96,97).…”
Section: Nebulized Beta-agonists In Hfmentioning
confidence: 99%
“…For patients similar to those in the present study, daily treatment by IPPB and somewhat lower doses (2.5-5 mg) of salbutamol have been recommended [Ben nis and Svedmyr, 1977;Shenjield et al, 1973;Spilzer et al, 1972]. Ruffin et al [1978b] found no significant differences between the peak bronchodilator effects of 1 and 5 mg of salbutamol in solution.…”
Section: Discussionmentioning
confidence: 41%
“…A report on a radiotracer technique [Ruffin et al, 1978a] indicates that a dose of about 30 pg of fenoterol in the airways produces maxi mal bronchodilation. Since it has been es timated that about 10% of a dose inhaled using IPPB reaches the lungs [ Ruffin et al, 1978b;Shenfield et al, 1973], it can be pre dicted that about 0.3 mg of fenoterol will cause maximal bronchodilation when ad ministered in this way. The dose used in the present study was of a similar order of magnitude.…”
Section: Discussionmentioning
confidence: 99%